Research and development of a smart helmet for enhanced safety and functionality of motorcycle riders - Musa, Adekunle Ibrahim; Adeyemi, Ayokunnumi; Olajide, Samuel (Journal of Production Engineering, 2025)
Motorcycles are a widely used mode of transportation in Nigeria, but they are also associated with high rates of road traffic accidents and fatalities. This study focuses on the research and development of an intelligent helmet to enhance the safety of motorcycle riders in the country. The helmet integrates advanced technologies such as impact sensors, alcohol detection, GPS tracking, and proximity sensors to monitor rider safety and environmental conditions. A prototype was developed using affordable components to ensure accessibility for low-income riders. Field trials demonstrated high accuracy in detecting collisions (95%), intoxication (98%), and obstacles within a 2-meter radius. Feedback from users indicated the helmet was comfortable, functional, and easy to use. The study concludes that intelligent helmets have the potential to significantly reduce motorcycle-related fatalities in Nigeria. However, challenges such as weather resistance and large-scale adoption need to be addressed. Future work should focus on improving the design, integrating renewable energy solutions, and collaborating with stakeholders for implementation.